Tamoxifen-induced acute pancreatitis – a case report - Czyżykowski, Rafał; Połowinczak-Przybyłek, Joanna; Janiak, Anna; Herman, Jerzy; Potemski, Piotr (Menopause Review/Przegląd Menopauzalny, 2014)
Tamoxifen is a selective estrogen receptor modulator used for the treatment of oestrogen/progesterone receptor positive breast cancer. It has antagonistic or agonistic activity depending on the tissue location. Generally it causes mild and reversible side effects, however more serious ones including cardiovascular and thromboembolic adverse events, uterine cancer or acute pancreatitis can also occur. Tamoxifen, like oestrogens, increases the plasma level of TG and liver secretion of VLDL. Moreover, it inhibits the key enzymes of triglyceride metabolism. In this report we present a case of a 55-year-old woman with a history of a poorly controlled hypertriglyceridaemia diagnosed with breast cancer. She was treated with surgery and adjuvant chemotherapy, radiotherapy and hormonotherapy with tamoxifen. About three months after hormonal treatment, her triglyceride level increased. Five months later she developed an acute necrotic pancreatitis that required hospitalization. Her serum samples on admission were highly lipemic. An abdominal ultrasound showed no evidence of gallstones or dilation of the bile ducts. There was no history of alcohol abuse or abdominal trauma. Tamoxifen was suspected as a trigger factor for pancreatitis. After the drug withdrawal and administration of the conservative management the patient’s medical condition improved. Due to a postmenopausal status of the patient and no harmful effect on serum lipids, an adjuvant hormonotherapy with aromatase inhibitor was started.